Code-Carrying Authorization - Maffeis, Sergio; Abadi, Martín; Fournet, Cédric; Gordon, Andy (13th European Symposium on Research in Computer Security, Málaga, Spain, October 6-8, 2008. Proceedings, 2008)
In authorization, there is often a wish to shift the burden of proof to those making requests, since they may have more resources and more specific knowledge to construct the required proofs. We introduce an extreme instance of this approach, which we call Code-Carrying Authorization (CCA). With CCA, access-control decisions can partly be delegated to untrusted code obtained at run-time. The dynamic verification of this code ensures the safety of authorization decisions. We define and study this approach in the setting of a higher-order spi calculus. The type system of this calculus provides the needed support for static and dynamic verification.